The unexplored influences of modern physics on john r. Commons economic theory - Ribeiro Guedes, Sebastião Neto [UNESP]; Jerônimo, Rodrigo Constantino [UNESP] (FapUNIFESP (SciELO), 2021)
Previous works of John R. Commons’ interpreters have emphasized the influence of numerous theoretical-methodological references (e.g., pragmatism, evolutionism, etc.) in shaping his economic thought. However, almost no mention is made of the influence of particle and relativity physics, which, as we debate, provide sources of insights to his work. This paper explores these connections by showing that John R. Commons was not only interested in the advances of that science but was also inspired by them to produce parallels and analogies that allowed his theory to escape the pitfalls of individualism and determinism while incorporating time and space in an innovative way in the economic discourse.
As influências inexploradas da física moderna na teoria econômica de John R. Commons
Keywords: Institutional economics; John R. Commons economic theory; Modern physics